Phonon-assisted oscillatory exciton dynamics in monolayer MoSe2. (December 2017) - Chow, Colin; Yu, Hongyi; Jones, Aaron; Schaibley, John; Koehler, Michael; Mandrus, David; Merlin, R.; Yao, Wang; Xu, Xiaodong
Abstract In monolayer semiconductor transition metal dichalcogenides, the exciton–phonon interaction strongly affects the photocarrier dynamics. Here, we report on an unusual oscillatory enhancement of the neutral exciton photoluminescence with the excitation laser frequency in monolayer MoSe2 . The frequency of oscillation matches that of the M-point longitudinal acoustic phonon, LA(M), suggesting the significance of zone-edge acoustic phonons and hence the deformation potential in exciton-phonon coupling in MoSe2 . Moreover, oscillatory behavior is observed in the steady-state emission linewidth and in time-resolved PLE data, which reveals variation with excitation energy in the exciton lifetime. These results clearly expose the key role played by phonons in the exciton formation and relaxation dynamics of two-dimensional van der Waals semiconductors. Exciton dynamics: monolayer MoSe2 features oscillatory enhancement of the photoluminescence spectrum The photoluminescence arising from the neutral exciton in monolayer MoSe2 exhibits an oscillatory enhancement with the excitation frequency. A team led by Xiadong Xu at the University of Washington performed steady-state and time-resolved photoluminescence spectroscopy as a function of the excitation energy, and observed that the MoSe2 neutral exciton photoluminescence intensity and linewidth oscillate with a period corresponding to the energy of the longitudinal acoustic phonon at the M point, LA(M). This indicates that phonons at the edge of the Brillouin zone dominate the exciton-phonon coupling and hot-carrier cooling in monolayer MoSe2 . Fine structures originating from resonant Raman scattering could also be identified nested within the photoluminescence spectra, with linewidths significantly smaller than those of ordinary photoluminescence. These results highlight the primary role of intervalley excitonic transitions in 2D semiconductors.